Impact of COVID-19 pandemic on maternofetal outcome in pregnant women with severe anemia - Meenakshi Singh; Manju Puri; Vidhi Choudhary; Aishwarya Kapur; G S Triveni; Gunjan; Manisha Patel; Vinita Kumari (Wolters Kluwer Medknow Publications, 2023)
Background: Anemia is the most common nutritional disease in pregnancy with significant adverse maternofetal outcome. The objective of the present study is to study the impact of COVID-19 pandemic on the pregnancy outcomes of women with severe anemia. Methodology: A retrospective observational study was conducted in the Department of Obstetrics and Gynaecology at LHMC and SSK Hospital, Delhi. The study included all antenatal women admitted at a gestational age of >26 weeks (third trimester) with severe anemia and hemoglobin level of 7 g/dL. In our study, a total of 4031 women were included as cases during study period (July to December 2022) and 6659 women as controls from pre-COVID-19 period (July to December 2019). Results: In present study, a total of 4031 women delivered during study period as compared to 6659 in control period. In the present study, the prevalence of anemia was observed to be 74.7% in the study group and 51.6% in the control group (P < 0.001). Mean hemoglobin level was significantly lower in study group as compared to the control groups P<0.05. Microcytic hypochromic anemia was the most common morphological type of anemia in both groups. Serum ferritin, serum iron, serum B12, and folic acid levels among cases were significantly (P < 0.05) lower as compared to controls. Odds of fetal growth restriction were 1.4 times higher among study group as compared to control groups. The odds of newborn complications such as low birth weight were 2.49 (95% CI: 1.04-5.91) and need for nursery or NICU admission were 4.84 times (95% CI: 0.48-48.24) higher in cases as compared to controls. Low birth rate was higher in cases and was found to be statistically significant. Conclusion: COVID-19 pandemic had indirect impact on adverse maternal and fetal outcome in women with severe anemia.